Individual and work related factors associated with symptoms of musculoskeletal complaints. II. Different risk factors among sewing machine operators. Issue 3 (March 1992) - Westgaard, R H; Jansen, T
Abstract : Individual and work related risk factors in the development of occupational musculoskeletal complaints were studied in a group of 210 female production workers, mainly sewing machine operators. Another group of 35 female employees performing secretarial or laboratory duties were also included. The production workers had significantly higher symptom scores with respect to self reported musculoskeletal complaints than the group with more varied work tasks for the head, neck, shoulders, and arms, but not for the low back, hips, and the lower extremities. No significant differences were found in symptom level between geographically separate groups of production workers with similar work tasks. The main individual risk factor identified in this study was the experience of previous, similar symptoms in the same body region, but this factor only accounted for 2-3% of total variance in symptom score for the neck and shoulders. Other individual factors of importance for symptoms in the neck and shoulders were "signs of psychological problems" and "tendency of muscle tension, " but these only account for about 1% of total variance in symptom score. Symptoms in the head and low back showed complex relations with individual parameters.